Compressive strength of the 5cmx5cm coconut empty fruit bunch fiber reinforced cement cubes - Muhammad Daniel Haiqal, Mansor; Noor Mazni, Ismail (Penerbit UMP, 2022)
As coconut cultivation expands, billions of tonnes of coconut waste, including empty fruit bunches (EFB) fibres are generated annually and mostly disposed in the landfills. The increase in environmental concern pertaining disposal of waste has leads to an interest to use empty fruit bunch (EFB) fibre from coconut waste as an alternative reinforcement in the construction materials, as presented in this research. The objectives of this research are to fabricate coconut EFB fibre reinforced cement cubes, investigate the effectiveness of the fibres in improving the compressive strength of the cement cubes, and also to analyse the fractured surface of the cubes after the compressive strength test. The cement cubes of 5cm x 5cm were prepared by mixing the cement, water, and coconut EFB fibres at several mixing designs. In comparison to the control-plain cement cubes, the compressive strength of the fibre reinforced cement cubes improved with the addition of the coconut EFB fibres by 1.6 times. The fractured surface analysis on the compressed cement cubes revealed that the control-plain cement cubes shatter into many pieces and completely parted. Meanwhile, in the EFB fibre reinforced cement cubes, the fractured pieces remain attached due to the bridging action by the coconut EFB fibre.